Observation of π-hole interactions in the solid state structures of three new copper(II) complexes with a tetradentate N4 donor Schiff base: Exploration of their cytotoxicity against MDA-MB 468 cells. (17th February 2017) - Khan, Samim; Al Masum, Abdulla; Islam, Md. Maidul; Drew, Michael G.B.; Bauzá, Antonio; Frontera, Antonio; Chattopadhyay, Shouvik
Graphical abstract: π-Hole interactions in solid state structure of three new mononuclear copper(II) complexes have been identified. The energetic features of these interactions have been studied by means of DFT calculations and characterized using Bader's AIM theory. Cytotoxicity of these complexes has also been explored. Abstract: A new mononuclear copper(II) complex, [CuL(ClO4 )2 ]·CH3 CN (1 ) has been synthesized from a symmetrical tetradentate di-Schiff base, N, N ′-bis(1-pyridin-2-yl-ethylidene)-2, 2-dimethylpropane-1, 3-diamine (L) and characterized by X-ray crystallography. Reactions of1 separately with ammonium thiocyanate and sodium azide yielded [CuL(NCS)]ClO4 (2 ) and [CuL(N3 )]ClO4 (3 ) respectively, both of which have also been characterized by single crystal X-ray diffraction analysis. The ability of the imidic CN bond of the metal-coordinated Schiff base ligand to interact with electron rich atoms in these complexes has also been studied by means of DFT calculations. The complexes showed high in vitro cytotoxic properties against MDA-MB 468 cells. The cells treated with these complexes gave bright green fluorescent light, indicating successful uptake of these complexes inside the nuclei of these cells.